Reassessing the foreign ownership wage premium in Germany - Hartmut Egger; Elke J. Jahn; Stefan Kornitzky (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
This paper evaluates the effect of foreign takeover on wages of workers in German establishments, using rich linked employer-employee data from 2003 to 2014. To identify a causal effect of foreign takeover, we combine propensityscore matching with a difference-in-difference estimator. We find that a takeover by a foreign investor leads to a wage premium of 4.0 log points in the year after ownership change, which further increases to 6.3 log points three years after acquisition. The wage premium is largest for high-skilled workers and higher for managers than for non-managers. We also show that the wage premium does not pick up an exporter effect due to a platform investment of the foreign owner, that it takes four to five years before it fully develops, and that the wage increase is specific to foreign acquisition instead of ownership change per se.
Keywords: F14; F16; F23; 330; Foreign ownership wage premium; Impact vs. adjustment effects; Propensity-score matching; Difference-in-difference estimation